INFLUENCE OF DROPLET SIZE ON SPRAY DEPOSITION AND WEED CONTROL USING GLYPHOSATE - Oliveira,Osmar G. T. M. (2021)
ABSTRACT Droplet size is one of the most important factors that affect spray deposition and weed control through the use of herbicides. The aim of this study was to evaluate the influence of the droplet size on the spray deposition and control of Euphorbia heterophylla and Urochloa ruziziensis by using glyphosate. The treatments included spraying glyphosate with fine, medium, coarse, very coarse, and ultra-coarse droplet sizes to determine the deposition, uniformity of distribution, visual control, and dry weight reduction (DWR). The treatments were compared with the values of the dose required to achieve 50% DWR or 50% visual control (C50) at 7, 14, 21, and 28 days after herbicide application. Fine and medium droplet sizes afforded high deposition values and low distribution uniformities in E. heterophylla . Fine and medium droplet sizes yielded the lowest C50 on visual control and DWR in E. heterophylla, respectively. The droplet size did not affect the spray deposition on U. ruziziensis plants; however, the larger droplets had less uniformity of distribution. In U. ruziziensis plants, spraying glyphosate with coarse and medium droplet sizes yielded the lowest values of C50 to visual control and DWR, respectively.